A sui generis electrode-driven spatial confinement effect responsible for strong twisting enhancement of floppy molecules in closely packed self-assembled monolayers - Bâldea, Ioan (Physical chemistry, chemical physics, 2018)
At present, it is widely accepted that properties (e.g., molecular conformation) of molecules adsorbed to form self-assembled monolayers (SAMs) on electrodes can be very different from isolated species because of a substantial charge transfer or specific chemical bonding at the interface. Contrary to this view, the theoretical results presented here predict that the strong twisting angle (φ) enhancement of floppy molecules adsorbed to form densely packed SAMs on most common electrodes (Pt, Au, Ag, and Cu) is neither due to charge transfer nor to specific bonding but rather to a sui generis electrode-driven spatial confinement effect that can be quantitatively described within an electrode-free two-dimensional model. We predict a logistic (“Fermi-Dirac”) growth pattern of φ as the coverage approaches the value characteristic of a herringbone arrangement, which is twice the value for isolated molecules or low-coverage SAMs.